2015
DOI: 10.1007/s10986-015-9266-z
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian limits of empirical multiparameter K-functions of homogeneous Poisson processes and tests for complete spatial randomness

Abstract: Abstract. We prove two functional limit theorems for empirical multiparameter second moment functions (generalizing Ripley's K-function) obtained from a homogeneous Poisson point field observed in an unboundedly expanding convex sampling window W n in R d . The cases of known and unknown (estimated) intensity lead to distinct Gaussian limits and require quite different proofs. Further we determine the limit distributions of the maximal deviation and the integrated squared distance between empirical and true mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The authors often observed such a behavior in their statistical work and believe that it is a somewhat intuitive knowledge in the statistical community. Fortunately, there is theoretical work on central limit theorems which confirms these empirical findings and gives them a theoretical explanation for spatially homogeneous (and isotropic) point processes (Heinrich andKlein 2014, Heinrich 2015).…”
Section: Facts On the Variability Of Estimators Of Summary Functionsmentioning
confidence: 82%
“…The authors often observed such a behavior in their statistical work and believe that it is a somewhat intuitive knowledge in the statistical community. Fortunately, there is theoretical work on central limit theorems which confirms these empirical findings and gives them a theoretical explanation for spatially homogeneous (and isotropic) point processes (Heinrich andKlein 2014, Heinrich 2015).…”
Section: Facts On the Variability Of Estimators Of Summary Functionsmentioning
confidence: 82%
“…is tight in Skorokhod topology [24,Lemma 3]. In this context, we note that condition (8.4) of [24,Lemma 3] follows from the variance upper bound derived in Proposition 9.2 and that similar as in (2.18) [22], we have replaced the equality in (8.5) of [24,Lemma 3] by an inequality. Combining this property with the convergence of finite-dimensional distributions yields the asserted weak convergence.…”
Section: Proofs Of Theorem 32 and Corollary 33mentioning
confidence: 95%
“…where the sequence (W n ) n∈N consists of increasing, convex and compact sets in R d with inball radius r(W n ) −→ n→∞ ∞, see, e.g. [7].…”
Section: Strong Brillinger-mixing Property Of Stationary α-Dpps With mentioning
confidence: 99%
“…At the beginning of this final section, we generalize a CLT proved in [7] for stationary Poisson processes on R d with the aim to establish a goodness-of-fit tests for the K-functions of stationary α-DPPs defined by (3.3). For this purpose, let…”
Section: Some Applications To Statistical Second-order Analysis Of Stmentioning
confidence: 99%
See 1 more Smart Citation